Understanding radical change: An examination of management departments in German-speaking universities - Marina Fiedler; Isabell Welpe; Arnold Picot (Management Revue, 2010)
Can radical organizational change be better achieved through planned change measures or through change measures developed as part of an evolutionary process? Based on 20 open interviews as well as recent survey data from 236 junior faculty members and 382 senior faculty members from departments of management at German universities and other academic institutions, this study suggests that the value commitment of the relevant stakeholders is greater to evolutionarily-developed rather than planned change measures, which consequently results in the dominant influence of the evolutionary change measures. Our results support the notion that in contexts that resemble the situation of universities in Germany - namely multi-polar power distribution and demanding preference structures within the affected group - successful radical organizational change management necessitates that the organization develops suitable change measures in an evolutionary way in order to achieve its goals.
Keywords: 650; organizational change; intra-organizational change; institutional change; planned change; evolutionary change